Anthropogenic influence on the drivers of the Western Cape drought 2015–2017. (29th November 2018) - Otto, Friederike E L; Wolski, Piotr; Lehner, Flavio; Tebaldi, Claudia; van Oldenborgh, Geert Jan; Hogesteeger, Sanne; Singh, Roop; Holden, Petra; Fučkar, Neven S; Odoulami, Romaric C; New, Mark
Abstract: In the period 2015–2017, the Western Cape region has suffered from three consecutive years of below average rainfall—leading to a prolonged drought and acute water shortages, most prominently in the city of Cape Town. After testing that the precipitation deficit is the primary driver behind the reduced surface water availability, we undertake a multi-method attribution analysis for the meteorological drought, defined in terms of a deficit in the 3 years running mean precipitation averaged over the Western Cape area. The exact estimate of the return time of the event is sensitive to the number of stations whose data is incorporated in the analysis but the rarity of the event is unquestionable, with a return time of more than a hundred years. Synthesising the results from five different large model ensembles as well as observed data gives a significant increase by a factor of three (95% confidence interval 1.5–6) of such a drought to occur because of anthropogenic climate change. All the model results further suggest that this trend will continue with future global warming. These results are in line with physical understanding of the effect of climate change at these latitudes and highlights that measures to improve Cape Town's resilience to future droughts are an adaptation priority.